(untitled) (AYUSHDHARA, 2025)
Climacteric symptoms encompass a broad range of physical, emotional and psychological manifestations that affect women during the menopausal transition. Despite their prevalence, these symptoms often remain underreported and undertreated, particularly in rural areas where access to healthcare services is limited. This cross-sectional survey aimed to evaluate the prevalence and severity of climacteric symptoms in women residing in Shiroda village. A total of 200 women aged 40-55 years participated in the survey. The survey collected data on demographic characteristics, menstrual history, reproductive history, lifestyle factors and mainly climacteric symptoms. A validated questionnaire was used to assess the presence and severity of climacteric symptoms, including hot flashes, irritability, joint pain, night sweats, vaginal dryness, mood swings and sleep disturbances. The present study highlighted that 92% of females suffer from psychoneurological symptoms, 53% of females suffer from pain (joint, lower back and muscle pain), and 38% of females suffer from hot flashes and irregular periods is around 30% in menopausal age. The findings of this study highlight the need for increased awareness and access to healthcare services for menopausal women in rural areas. Healthcare providers should prioritize the diagnosis and treatment of climacteric symptoms and women should be empowered to seek medical attention for symptoms.